Kedudukan Hukum Perkawinan Dengan Adanya Pemalsuan Identitas Dalam Perkawinan - Restu Pertiwi, Yulinda; Fatahullah, Fatahullah (Private Law, 2024)
The purpose of the study is to determine the legal validity of marriage in the presence of identity falsification in marriage and to determine the validity and legal consequences of identity falsification in same-sex marriages. This type of research is normative legal research. The types of legal materials use primary, secondary, and tertiary legal materials. The results of this study that the legal validity of marriage in the presence of falsification of identity in marriage, namely that the marriage is considered invalid. So if a marriage occurs between people of the same sex, the legal consequence for that marriage is null and void.